2014
DOI: 10.1007/s00265-014-1835-3
|View full text |Cite
|
Sign up to set email alerts
|

Consistent individual differences in paternal behavior: a field study of three-spined stickleback

Abstract: Consistent individual differences in parenting are widespread; however, we know little about why there is variation in parenting behavior among individuals within species. One possible explanation for consistent individual differences in parenting is that individuals invest in different aspects of parental care, such as provisioning or defense. In this field study we measured consistent individual differences in parenting behavior and evaluated correlations between parenting and other behaviors in threespine s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
22
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 62 publications
(27 citation statements)
references
References 52 publications
5
22
0
Order By: Relevance
“…Across all freshwater populations, males exposed to the dragonfly naiad on average showed reduced parental care for 1 day before converging on similar fanning behavior to control individuals that did not experience predation risk (Figs. & ), similar to previous studies in stickleback with piscivorous predators (Stein & Bell ; Stein & Bell ).…”
Section: Resultssupporting
confidence: 89%
See 4 more Smart Citations
“…Across all freshwater populations, males exposed to the dragonfly naiad on average showed reduced parental care for 1 day before converging on similar fanning behavior to control individuals that did not experience predation risk (Figs. & ), similar to previous studies in stickleback with piscivorous predators (Stein & Bell ; Stein & Bell ).…”
Section: Resultssupporting
confidence: 89%
“…Males from well‐established populations, which experienced many generations of selection in freshwater, dramatically decreased parenting when the predator was present. This result is consistent with previous studies, which have shown that male sticklebacks from populations that experience high levels of predation by piscivorous fishes decrease parenting both in the presence of an immediately after predation risk (Stein & Bell ; Stein & Bell ; Stein & Bell ). It is likely that the reason why males (on average) from marine populations did not change their behavior in response to the predator was because they did necessarily perceive the dragonfly—a novel predator to marine sticklebacks—as a threat.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations